Validity of a novel device for indoor analysis of cyclists` drag area - Ordiñana-Pérez, M.; Mateo-March, M.; Monteagudo, P.; Zabala, M.; Blasco-Lafarga, C. (European Journal of Sport Science, 2023)
Purpose: Cyclists need to measure aerodynamic resistance accurately and reliably, as well as economically. Devices such as Notio Aerostick, an equipment device that includes one pitot tube, have appeared for this purpose. The aim of this study is, therefore, to test the reliability and degree of agreement in the evaluation of the CdA (coefficient of aerodynamic drag), assessed by means of the Notio Aerostick compared to the Virtual Elevation (VE) and Martin mathematical models. Method: Seventeen professional cyclists rode in a 250-metre-long velodrome covered with a concrete surface with their own time trial bikes. Each cyclist completed three rides of 15 laps at constant speed for the evaluation of the CdA, each of them in a different position [Baseline (B), Change 1 (C1) and Change 2 (C2)]. Results: The differences in CdA between methods were found for Martin in comparison with VE in all positions (p <.001) and with Notio Aerostick in B and C2 (p> .05). About differences of CdA for each method, considering between position changes, the results were the same for VE and Martin, but different for Notio Aerostick. Conclusions: Findings suggest that, notwithstanding Notio Aerostick is valid if we compare CdA values with respect to VE, since the direction of their between-positions CdA changes differs, the results of their aerodynamic evaluation could lead us to recommend different final setups. We need studies that evaluate different units of the Notio Aerostick device as well as the reliability and precision of each sensor that includes Notio Aerostick.